A Methodological Study for the Stress Analysis to Evaluate Single Lap Adhesive Joint. Issue 1 (May 2021) - Kushwah, Sagarsingh; Bhatt, Meet; Desai, Chirag; Parekh, Shreyashkumar; Joshi, Poojan
Abstract: The use of adhesive bonding is increased in load-bearing applications in place of conventional joining techniques such as bolted or rivets joints. The high-stress concentration occurs at the end of an adhesive-bonded lap joint so all failures begin at the end of the overlap region and get fractured in the end. The single-lap adhesive-bonded joint was used in the current study to examine the peel stress and shear stress results along the overlap region. The comparison of the analytical and experimental result was made to validate the results along with it the load vs displacement curve was obtained from results. Also, stress vs strain curve and peel stress vs overlap length of the one mm thickness of testing specimen was obtained.